Systems-Based Approaches to Unravel Networks and Individual Elements Involved in Apple Superficial Scald - Karagiannis, Evangelos; Tanou, Georgia; Scossa, Federico; Samiotaki, Martina; Michailidis, Michail; Manioudaki, Maria; Laurens, François; Job, Dominique; Fernie, Alisdair R.; Orsel, Mathilde; Molassiotis, Athanassios (Frontiers in Plant Science, 2020)
Superficial scald is a major physiological disorder in apple fruit that is induced by cold storage and is mainly expressed as brown necrotic patches on peel tissue. However, a global view of the gene-protein-metabolite interactome underlying scald prevention/sensitivity is currently missing. Herein, we found for the first time that cold storage in an atmosphere enriched with ozone (O3) remarkably induced scald symptoms in ‘Granny Smith’ apple fruits during subsequent ripening at room temperature. In contrast, treatment with the ethylene perception inhibitor 1-methylcyclopropene (1-MCP) totally reversed this O3-induced sclad effect. Amino acids, including branched-chain amino acids, were the most strongly induced metabolites in peel tissue exposed to 1-MCP. Proteins involved in oxidative stress and protein trafficking were differentially accumulated prior and during scald development. Genes involved in photosynthesis, flavonoid biosynthesis and ethylene signaling displayed significant alterations in response to 1-MCP and O3. Analysis of regulatory module networks identified putative transcription factors (TFs) that could be involved in scald. Subsequently, a transcriptional network of the genes-proteins-metabolites and the connected TFs was constructed. This approach enabled identification of several genes co-regulated by TFs, notably encoding glutathione S-transferase (GST) protein(s) with distinct signatures following 1-MCP and O3 treatments. Overall, this study will be an important contribution to future functional studies and breeding programs for this fruit crop, aiding to the development of improved apple cutlivars to superficial scald.